Construction of ZnO–SnO2 n-n junction for dual-sensing of nitrogen dioxide and ethanol. (November 2020) - Zhao, Sikai; Shen, Yanbai; Zhou, Pengfei; Li, Guodong; Hao, Fulai; Han, Cong; Liu, Wenbao; Wei, Dezhou
Abstract: As inspired by the recent reports that many unique properties can be achieved by using two dissimilar components to form heterostructures, especially for materials in nano-size. In this letter, one-dimensional ZnO–SnO2 heterostructures were constructed by uniformly growing SnO2 nanoparticles on the surfaces of ZnO nanowires. Compared with pure ZnO nanowires, ZnO–SnO2 heterostructures exhibited significant enhancement in response and selectivity to NO2 and ethanol. The excellent response/recovery characteristics and stability of ZnO–SnO2 heterostructures demonstrate that the heterostructure construction is promising for dual sensing of NO2 and ethanol using one sensor. The possible enhancement sensing mechanisms were discussed based on the depletion control and potential barrier control models. Highlights: A facile strategy was developed to synthesis core-shell-like ZnO–SnO2 n-n hetero-structured nanowires. ZnO–SnO2 nanowires consisted of ZnO nanowires and ultra-fine SnO2 nanoparticles. The density of SnO2 nanoparticles that grown on the surface of ZnO nanowires was controllable. ZnO–SnO2 hetero-structured nanowires exhibited an excellent dual-sensing ability to NO2 and ethanol.